Analisis Komparatif Kebijakan Blue Carbon Di Indonesia Dan Meksiko - Harefa, Remember to; Dompak, Timbul; Harefa, Erwin; Salsabila, Lubna (Prosiding, 2024)
This study does a comparative examination of blue carbon policies in Indonesia and Mexico, two countries well-known for their vast coastal ecosystems that are abundant in mangroves and seagrasses. This paper analyzes the policy frameworks, implementation techniques, and effects of blue carbon conservation efforts in both countries. Indonesia has enacted strong policies, such as the National Action Plan on Climate Change Adaptation and the National Mangrove Management Strategy, which prioritize community-based management and cooperation between the public and private sectors. This strategy has resulted in a rise in the extent of mangrove forests, improved the functioning of ecosystems, and strengthened the ability to capture and store carbon. In a similar vein, Mexico has implemented extensive frameworks through the National Climate Change Strategy and the General Law on Climate Change, which aim to foster collaboration among stakeholders and encourage the adoption of sustainable management practices. Positive developments in Mexico include the expansion of mangrove regions and the enhancement of biodiversity conservation. Notwithstanding these achievements, both countries continue to face problems in terms of securing long-term funding, ensuring effective coordination among stakeholders, and mitigating the implications of climate change. Subsequent studies should prioritize the improvement of governance structures, the enhancement of monitoring systems, and the expansion of successful initiatives to guarantee the enduring viability of global blue carbon conservation endeavors.